2014
DOI: 10.1021/nn502829s
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport and Grain Growth in Solution-Cast, Chloride-Terminated Cadmium Selenide Nanocrystal Thin Films

Abstract: We report the evolution of electrical transport and grain size during the sintering of thin films spin-cast from soluble phosphine and amine-bound, chloride-terminated cadmium selenide nanocrystals. Sintering of the nanocrystals occurs in three distinct stages as the annealing temperature is increased: (1) reversible desorption of the organic ligands (≤150 °C), (2) irreversible particle fusion (200–300 °C), and (3) ripening of the grains to >5 nm domains (>200 °C). Grain growth occurs at 200 °C in films with 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 58 publications
2
68
0
Order By: Relevance
“…Second, we can prevent formation of trap states and recombination sites while maintaining strong electronic coupling by using nonvolatile PEG-thiolate ligands instead of using chloride, 22 thiocyanate, 25 sulfide, [26][27][28] metal chalcogenide complexes, 13,[29][30][31] tetrafluoroborate, 23,24 hydrazine, 14,32 or pyridine. 19 Third, SNCs coated with either small molecules or various ions are susceptible to undergoing fast oxidation even at ambient conditions 19 making processing during device fabrication very difficult.…”
Section: 32mentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we can prevent formation of trap states and recombination sites while maintaining strong electronic coupling by using nonvolatile PEG-thiolate ligands instead of using chloride, 22 thiocyanate, 25 sulfide, [26][27][28] metal chalcogenide complexes, 13,[29][30][31] tetrafluoroborate, 23,24 hydrazine, 14,32 or pyridine. 19 Third, SNCs coated with either small molecules or various ions are susceptible to undergoing fast oxidation even at ambient conditions 19 making processing during device fabrication very difficult.…”
Section: 32mentioning
confidence: 99%
“…Use of this property of the SNC films would open a new frontier of scientific research by enabling the preparation of "artificial solids" with unprecedentedly high conductivity. 17 A number of methods have been developed to enhance the electronic coupling between SNCs in colloidal dispersion and/or solid films by exchanging the native bulky, hydrocarbon ligands with small organic ligands, [18][19][20][21] inorganic ions, [22][23][24][25][26][27][28] and metal chalcogenide complexes. 13,[29][30][31] The solid phase ligand exchange reaction can cause a dramatic structural rearrangement of SNCs, which results in the appearance of cracks and voids in the solid films or irreversible aggregation of SNCs inside the films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has invoked some skepticism as to whether the observed effects are in part due to necking and local fusion of QDs, upon which percolative pathways with greatly altered transport properties could form [27]. In such a situation, the genuine physics of QDs may not be applicable anymore such that a careful distinction between real QD solids with high mobilities and those with favorable transport properties due to macroscopic percolative pathways is important.…”
Section: Kang Et Al Have Measured Quantum Dot Solids Composed Of Cdsmentioning
confidence: 99%
“…Longer-chain amines as ligands have been demonstrated to aid colloidal stabilization and improve surface passivation in CdSe CQDs. 18,19 We found that hexylamine (HXA) could completely redisperse the quantum dots. However, due to its higher boiling point, the resulting films were comparable in thickness to those made from BTA.…”
mentioning
confidence: 99%